Interorganisational Collaboration Workflow Challenges and the Potential of Technology Integration for E-Payment Process Improvement: A Case Study of a Malaysian Public Sector Agency - Khairil Faizal Khairi; Naharudin Saadan (Penerbit Universiti Kebangsaan Malaysia (UKM Press), 2026)
Indexed by MyCite